HUBUNGAN ANTARA FASILITAS DAN KBM OLAHRAGA DENGAN PERILAKU HIDUP SEHAT MAHASISWA FKIP UNIVERSITAS KRISTEN SATYA WACANA SALATIGA TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
HDI ( Human Development Index ) Indonesia is still low , one factor is the level of health . Necessary efforts habituation healthy behavior , such as smoking behavior , healthy diet and regular exercise to people in all groups . This research was a survey using a quantitative qualitative approach , the technique of obtaining data using interviews , observations and questionnaires were distributed to a sample of the student population numbered 308 students of 2316 . The results of this research shows that there are differences in health behavior between students FKIP SWCU , There are differences in health behavior FKIP student, among students who actively take part in KBM Sports with students who inactive but use the facility with t-value amounted to 8.37 . There are differences in health behavior between students who actively take part in KBM Sports with students who inactive and also does not use the facility with t value of 6.47 . There are differences in health behavior between students who do not actively but use the facility with students who inactive and also does not use the facility with t value of 6.11.